Antara Recognisi, Rekonstruksi dan Kekhawatiran Hilangnya Indigenousity Pondok Pesantren - Bahar Agus Setiawan; Sofyan Rofi (STAI Ma'had Aly Al-Hikam Malang, 2020)
The Pesantren are Islamic educational institutions that were born before Indonesian independence. Despite having a long history, skepticism always accompanies the output of pesantren in connection with its recognition. The independence and existence of Islamic boarding schools throughout their history has not yet become a consideration in terms of legality. The issuance of PMA policy number 18 of 2014 concerning the Mu'addalah education unit at Islamic Boarding School gives new hope to the recognition of graduates of pesantren. Changes that are a requirement for the legality of Pesantren Muddalah, provide its own problems and do not rule out reducing the indigenousity of the pesantren itself. This paper aims to analyze the Pesantren Mu'addalah policy based on literature review. The results of the study of this policy, first, the Muaddalah pesantren is a form of recognition (equalization / equality) for pesantren institutions, second, the policy requires curriculum changes to include general subjects, and third, the implementation of the policy must be understood in full so that recognition does not threaten indigenousity pesantren itself.Keyword : Policy, Muaddalah, pesantren.